2022
DOI: 10.1101/gad.349172.121
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar-based Dux repression is essential for embryonic two-cell stage exit

Abstract: Upon fertilization, the mammalian embryo must switch from dependence on maternal transcripts to transcribing its own genome, and in mice this involves the transient up-regulation of MERVL transposons and MERVL-driven genes at the two-cell stage. The mechanisms and requirement for MERVL and two-cell (2C) gene up-regulation are poorly understood. Moreover, this MERVL-driven transcriptional program must be rapidly shut off to allow two-cell exit and developmental progression. Here, we report that robust ribosomal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 81 publications
(138 reference statements)
6
38
0
1
Order By: Relevance
“…Indeed, sustained activation of the 2C-associated transcriptional program induces developmental arrest with blastomeres at the 4C stage having a 2C transcriptional signature 10 . Silencing of the 2C transcriptional program involves redundant but rather independent mechanisms, including transcriptional repression of the Dux gene by TRIM66, the E3 ligase PIAS4 or SMCHD1 as well as physical recruitment of Dux loci to nucleolar heterochromatin [11][12][13][14] . Furthermore, MERVL repeats are transcriptionally silenced by the protein complex ZMYM2/LSD1 or the chromatin remodeler CAF-1 and post-transcriptionally by the RNA decay complex NEXT [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, sustained activation of the 2C-associated transcriptional program induces developmental arrest with blastomeres at the 4C stage having a 2C transcriptional signature 10 . Silencing of the 2C transcriptional program involves redundant but rather independent mechanisms, including transcriptional repression of the Dux gene by TRIM66, the E3 ligase PIAS4 or SMCHD1 as well as physical recruitment of Dux loci to nucleolar heterochromatin [11][12][13][14] . Furthermore, MERVL repeats are transcriptionally silenced by the protein complex ZMYM2/LSD1 or the chromatin remodeler CAF-1 and post-transcriptionally by the RNA decay complex NEXT [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…3j). A recent report suggests reduced Duxf3 is necessary for embryo development beyond the 2-cell stage 37 . Thus.…”
Section: Maternal Ablation Of Eif4e1b Impairs Zgamentioning
confidence: 98%
“…In addition, when nucleoli were disrupted by blocking RNA polymerase I activity or preventing nucleolar phase separation, Dux loci can dissociate from the nucleolar surface and get activated, promoting the transition to 2CLCs ( Xie et al, 2022 ). In mouse embryos, rRNA biogenesis and nucleolus defect prevented nucleolar maturation, resulting in developmental arrest at the 2C–4C stage ( Zhu et al, 2021a ; Xie et al, 2022 ).…”
Section: Epigenetic Regulation Of Totipotencymentioning
confidence: 99%
“…During the cell cycle progression, dynamic remodeling occurs in the nucleolus ( Probst et al, 2009 ; Padeken and Heun, 2014 ; Nagano et al, 2017 ; Zhang H. et al, 2019 ). Immature nucleolus structure and reduced rRNA synthesis were found in 2CLCs and 2C embryos ( Xie et al, 2022 ). Interestingly, it was demonstrated that LIN28 could interact with the TRIM28/NCL complex to mediate the repression of Dux in mESCs and pre-implantation embryos ( Percharde et al, 2018 ; Sun et al, 2022 ).…”
Section: Cell Cycle and Dna Damage Response In Totipotencymentioning
confidence: 99%